2020
DOI: 10.2217/pmt-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Pain Management: A Review

Abstract: There is a complex interplay between sleep disturbance and patients in pain. There is an increasing appreciation of the direct effects of analgesic drugs and sleep quality. This review provides an overview of the effects of different analgesic drugs and their effects on phases of sleep. The effects of different pain conditions and their direct effects on sleep physiology are also discussed. A structured search of the scientific literature using MEDLINE and PubMed databases. Original human and animal studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 105 publications
1
13
0
Order By: Relevance
“…The present study also identified a strong relationship between the presence of delirium and pain, as assessed with the VAS. This association is consistent with the so-called multifactorial model of delirium, involving vulnerability and accumulation of multiple risk factors (Woo & Ratnayake, 2020). From this perspective, analgesia and sedation (and monitoring of their adequacy and depth) is a key measure in preventing, or managing, delirium in the ICU.…”
Section: Discussionsupporting
confidence: 82%
“…The present study also identified a strong relationship between the presence of delirium and pain, as assessed with the VAS. This association is consistent with the so-called multifactorial model of delirium, involving vulnerability and accumulation of multiple risk factors (Woo & Ratnayake, 2020). From this perspective, analgesia and sedation (and monitoring of their adequacy and depth) is a key measure in preventing, or managing, delirium in the ICU.…”
Section: Discussionsupporting
confidence: 82%
“…Longitudinal and experimental research has affirmed that disturbed sleep causes generalized hyperalgesia and reduced endogenous pain inhibition in healthy subjects [19,20]. Increased pain can, in turn, further disrupt sleep, leading to a vicious cycle that can be further exacerbated by pain medication adversely affecting sleep [21,22]. However, insomnia is increasingly assumed to be a primary determinant, as it both deteriorates existing pain and predicts pain onset [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is easy to ignore that sleep disturbance is also one of the main complaints of patients with rotator cuff injury (Khazzam et al, 2018b;Longo, 2022). Sleep disturbance can exacerbate pain and lead to negative emotions, behavior, and cognition in patients (Woo and Ratnayake, 2020). A previous study (Martin et al, 2018) reported the relationship between rotator cuff disease and sleep disturbance, and the correlation between preoperative sleep disturbance and postoperative pain in patients with rotator cuff injury is still unclear.…”
Section: Discussionmentioning
confidence: 99%